2017
DOI: 10.3892/ol.2017.7561
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin reverses the doxorubicin resistance of prostate cancer cells by downregulating the expression of c‑met

Abstract: Chemotherapy is an irreplaceable treatment for prostate cancer. However, the acquisition of chemoresistance is a common and critical problem that requires urgent solutions for the effective treatment of this disease. The aim of the present study was to determine whether the combination of quercetin with doxorubicin reversed the resistance of prostate cancer cells to doxorubicin-based therapy. A prostate cancer (PC)3 cell line (PC3/R) with acquired doxorubicin-resistance was established. A significant drug-resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…Quercetin may potentiate the effect of fludarabine and ABT-737 against CLL via Mcl-1 inhibition (220), enhance the efficacy of (1) Dox in the Dox resistant prostate cancer (PC)3 cell line (PC3/R) by down-regulating c-met (221) and Dox resistant human leukemic MDR K562/ADR cells by regulating JNK/MAPK (222), (2) TRAIL to pancreatic cancer cells through JNK-mediated cFLIP turnover (223), (3) tamoxifen in tamoxifen-resistant breast cancer cell line (MCF-7Ca/TAM-R) by up-regulating ERα and down-regulating Her-2 (224), etc.…”
Section: Multi-functional Flavonoids Overcome Mdr In Cancermentioning
confidence: 99%
“…Quercetin may potentiate the effect of fludarabine and ABT-737 against CLL via Mcl-1 inhibition (220), enhance the efficacy of (1) Dox in the Dox resistant prostate cancer (PC)3 cell line (PC3/R) by down-regulating c-met (221) and Dox resistant human leukemic MDR K562/ADR cells by regulating JNK/MAPK (222), (2) TRAIL to pancreatic cancer cells through JNK-mediated cFLIP turnover (223), (3) tamoxifen in tamoxifen-resistant breast cancer cell line (MCF-7Ca/TAM-R) by up-regulating ERα and down-regulating Her-2 (224), etc.…”
Section: Multi-functional Flavonoids Overcome Mdr In Cancermentioning
confidence: 99%
“…CYP1B1 inhibitors have also been shown to enhance the chemotherapeutic effects of DOX in several cancer cell lines including lung cancer [192][193][194], breast cancer [195][196][197][198][199][200][201], liver cancer [201][202][203][204], glioblastoma [205], prostate cancer [206], colorectal cancer [207,208], gastric cancer [209], and leukemia [210,211]. Importantly, several inhibitors have also been shown to overcome DOX resistance in DOX-resistant cancer cell lines [209,210,[212][213][214][215][216][217].…”
Section: Chemosensitizing Effects Of Cyp1b1 Inhibitorsmentioning
confidence: 99%
“…Protected from chronic DOX in rats [190,229] and mice [185] in vivo. Augmented the cardioprotective effect of losartan against chronic DOX cardiotoxicity [230] Enhanced DOX anti-cancer effects in xenografts of leukemia P388 cells [185], liver cancer cells [231], 4T1 breast cancer cells [232,233] Reversed chemoresistance to DOX in hepatocellular carcinoma cells [202], breast cancer cells [200,212], prostate cancer cells [206], multidrug-resistant leukemia K562 cells [210] Enhanced chemotherapeutic effect of DOX against human breast cancer cells [195][196][197]199,234], human colorectal HT29 cancer cell line [208], neuroblastoma cells [235] Luteolin 79 [219] Protected against DOX-induced cardiomyocyte toxicity in vitro [188] Attenuated acute DOX-induced myocardial lipid peroxidation in vivo [236] Luteolin ( [240] Induced CYP1B1 gene expression [241,242] Protected from chronic DOX-induced cardiotoxicity in vivo [243,244] Protected from DOX-induced senescence in vascular smooth muscle cells [191] Potentiated the cytotoxic effect of DOX in MCF-7, MCF-7/ADR cells, MDA-MB-231 (breast), PC-3 (prostate), H460 (lung), and BxPC-3 (pancreas) cancer cells [213,[245][246][247]] Attenuated DOX-induced cytotoxicity in MCF-7 breast cancer cells in one study [248] Sensitized diffuse large cell lymphoma to CHOP (cyclophosphamide, DOX, vincristine, prednisone) chemotherapy in SCID tumor-bearing mice in vivo [2...…”
Section: Chemosensitizing Effects Of Cyp1b1 Inhibitorsmentioning
confidence: 99%
“…Studies have reported that multiple natural drugs can be used as sensitizers in chemotherapy. For instance, imperatorin, a linear furanocoumarin compound extracted from the root of Angelica dahurica , has been reported to decrease the cisplatin resistance through suppression of MCL-1 [ 35 ]; Quercetin, a flavonoid that widely distributes in plant-based foods, has been found to reverse the resistance of prostate cancer to doxorubicin-based therapy [ 36 ]; Resveratrol, a natural polyphenol compound, has been proved to restore the sensitivity of glioma cells to temozolamide through inhibiting the activation of Wnt signaling pathway [ 37 ]. As one kind of natural drug, osthole has some anti-tumor activity with low toxicity and little side effects.…”
Section: Discussionmentioning
confidence: 99%